Upaya Meningkatkan Produktivitas Kerja Karyawan Dengan Metode 360 Degree Feedback - Tanto Heryanto; Elvira Febriana Puteri (Masoem University, 2023)
Employee productivity at MTS Husnul Khotimah has decreased, this is indicated by a lot of employee work that has not been completed in accordance with the predetermined time. The purpose of the study was to determine efforts to increase employee work productivity using the 360 degree feedback method, obstacles and solutions. The research approach used is quantitative and qualitative (mixed methods), and phenomenological research types. Primary data type with data collection methods through interviews and questionnaires. Quantitative data analysis methods (Likert scale), and qualitative data analysis (data reduction, data presentation, data verification and conclusions). The population in this study was 20 employees with a sample of nine employees and one madrasah head. Purposive sampling informant selection technique. The results showed that employee work productivity had a percentage range of 71% to 89% with strong to very strong interval criteria. It can be interpreted that employee work productivity in general is strong and even very strong. It can be interpreted that employee work productivity in general is strong and even very strong. However, there are still some obstacles in increasing employee work productivity such as employee placement or positions that are still not in accordance with graduate backgrounds and abilities, and it still takes a lot of time to complete the tasks that have been given.